VALDECANTOS, A. (2022). La modernidad póstuma. Madrid: Abada. - Chaves González, Julián (Daimon Revista Internacional de Filosofia, 2024)
Reseña del libro VALDECANTOS, A. (2022). La modernidad póstuma. Madrid, Abada.